MUHAMMADIYAH: CIVIL ISLAM DAN MASYARAKAT ISLAM YANG SEBENAR-BENARNYA - Asep Purnama Bahtiar (Tajdida: Jurnal Pemikiran dan Gerakan Muhammadiyah, 2016)
According to the conditions and resources-including social resource and organizational culture - owned by each structure and foundation lines as well as setting external (social, culture, politics, economy, etc.) that vary by region and area, the model of development of the true Islamic Society, at least be able to show three forms or models; First, the homogeneous MIyS model. MIyS is formed from components and members of the same community, all members are Muhammadiyah followers.  Second, intra-heterogeneous MIyS models. MIyS awakened from the Muslim community components but diverse organization (Muhammadiyah, Persis, NU, SI, Al-Irsyad, etc.); and Muhammadiyah became its leading sector. Third, extra-heterogeneous MIyS embodied in the reality of a pluralistic society religion, ethnicity, culture, politics, and so on. In this third model Muhammadiyah should really be extra smart and wise in building MIyS, so as not to cause turbulence and potential conflicts. Of the three models MIyS could also be seen as a civil Muhammadiyah dynamics of Islam civil or Islamic civil society that can manifest itself in scale and non-uniform type.